Contributory factors to the smoking of shisha among teenagers in the Perak City of Ipoh: A Preliminary qualitative survey - Khor, Poh Yen; Norshidah Harun,; Fazreenizam Ishak,; Nur Aimy Iryany Mohd Anuar,; Noraini Abdul Karim,; Aqirah Azman,; Tuan Suriana Tuan Mahmood, (Universiti Kebangsaan Malaysia, 2012)
The purpose of this study is to explore the reasons of Shisha smoking among teenagers in Ipoh, Perak. Methods Data was collected using in-depth face to face interview. Purposive convenient sampling was used to select volunteer respondents from one of the Shisha restaurant located at Ipoh. The interviews were conducted for 15- 20 minutes, recorded using video tape. The data obtained was transcribed and coded for the purpose of thematic analysis. Results All respondents were influenced by peers in their first attempt in Shisha smoking. Other reasons attracting them to continue smoking Shisha include appealing smell and the flavoured taste of Shisha, easy to access, perceived that Shisha was not addictive and its’ cheaper price. In terms of perception on health risk, all respondents believed that Shisha was less harmful compared to cigarette smoking Conclusions More educational programme, health talk about risk of Shisha should be developed and conducted to rectify the misconception about health risk of Shisha smoking. The target population should be focus on male teenagers who smoke Shisha in order to control the widespread Shisha smoking in Malaysia.